Peculiarities of terms of consumer and household services (linguistic-cultural aspect) - Ashurova, Z (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article considers the entry of consumer and domestic services into the non-production and production services sector. It turnedout that household services are distinguished by socio-economic methods and forms of directly satisfying the material and spiritual needs of people, regardless of their professional and social activities